2008
DOI: 10.1016/s0924-9338(08)70059-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of patients from different cultures in Germany

Abstract: Further analytical studies are needed to clarify health differences between these groups. Migrants are a heterogeneous group and only group-specific investigations will clarify associations between countries of origin, health status and use of health care institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 14 publications
5
41
1
10
Order By: Relevance
“…Firstly, the higher prevalence rates of depression for immigrant are confirmed by recent studies for Belgium [8;25], the Netherlands [28] and Sweden [34]. In Germany, our results are consistent with Glaesmer et al [26] who also found no elevated risk for depression among immigrants, but are in contrast with the study of Wittig et al [27], that showed higher depression scores for Vietnamese and Polish immigrants. The higher prevalence rates for depression among ethnic minorities in the UK is also shown by Weich et al [19] for some subgroups (middle-aged Pakistani men, older Indian and Pakistani women), while for others (Bangladeshi women) no differences with the native population are found.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, the higher prevalence rates of depression for immigrant are confirmed by recent studies for Belgium [8;25], the Netherlands [28] and Sweden [34]. In Germany, our results are consistent with Glaesmer et al [26] who also found no elevated risk for depression among immigrants, but are in contrast with the study of Wittig et al [27], that showed higher depression scores for Vietnamese and Polish immigrants. The higher prevalence rates for depression among ethnic minorities in the UK is also shown by Weich et al [19] for some subgroups (middle-aged Pakistani men, older Indian and Pakistani women), while for others (Bangladeshi women) no differences with the native population are found.…”
Section: Discussionsupporting
confidence: 92%
“…The response rate in Germany (56.3%) is comparable to studies examining Polish immigrants in Germany, for example, Merbach et al (2008) report a response rate of 47.5%, whereas the high response rate in Poland (82.5%) attracts attention. This could perhaps be explained by the fact that in Poland a relative large group of students had been recruited (larger than in Germany).…”
Section: Discussionsupporting
confidence: 59%
“…El tipo de trastorno psiquiátrico encontrado -trastornos de ansiedad, y los trastornos del ánimo-es similar al de otros estudios en el que evaluaron la salud mental de población de inmigrantes 11,25 . La prevalencia de trastornos mentales en la población inmigrante IJ es más alta que la de la población adulta inmigrante consultante al centro de salud primario (29,3% versus 17,8%).…”
Section: Discussionunclassified
“…En Europa, las cifras encontradas son variadas. En España, Bélgica y Alemania se encontró una mayor prevalencia de trastornos depresivos, de ansiedad y somatización en grupos inmigrantes, en comparación con la población nativa [9][10][11] . En Suiza, los inmigrantes provenientes de países de la ex-Unión Soviética, presentan tasas similares de sintomatología psiquiátrica comparado con los nacidos en Suiza, no así los inmigrantes provenientes de otros países del Este de Europa que presentan el doble de sintomatología psiquiátrica 5 .…”
unclassified